Use of Cardiac Injury Markers in the Postmortem Diagnosis of Sudden Cardiac Death - Octavio, Carvajal-Zarrabal; Patricia M., Hayward-Jones; Cirilo Nolasco, Nolasco-Hipólito; Dulce, Barradas-Dermitz; Ana Laura, Calderón-Garcidueñas; Noe, Lopez-Amador (Blackwell Publishing Inc., 2017)
In the daily practice of forensic pathology, sudden cardiac death (SCD) is a diagnostic challenge. Our aim was to determine the usefulness of blood biomarkers [creatine kinase CK-MB, myoglobin, troponin I and T (cTn-T & T), and lactate dehydrogenase] measured by immunoassay technique, in the postmortem diagnosis of SCD. Two groups were compared, 20 corpses with SCD and 8 controls. Statistical significance was determined by variance analysis procedures, with a post hoc Tukey multiple range test for comparison of means (P <0.05). SCD cases showed significantly higher levels (P <0.05) of cTn-T and cTn-I compared to the control group. Although only cases within the first 8 hours of postmortem interval were included, and the control group consisted mainly of violent death cases, our results suggest that blood troponin levels may be useful to support a diagnosis of SCD.